2018
DOI: 10.1002/eji.201747122
|View full text |Cite
|
Sign up to set email alerts
|

Microbial metabolites, short‐chain fatty acids, restrain tissue bacterial load, chronic inflammation, and associated cancer in the colon of mice

Abstract: The intestinal immune system is regulated by microbes and their metabolites. The roles of gut microbial metabolites in regulating intestinal inflammation and tumorigenesis are incompletely understood. We systematically studied the roles of short-chain fatty acids (SCFAs) and their receptors (GPR43 or GPR41) in regulating tissue bacterial load, acute versus chronic inflammatory responses, and intestinal cancer development. SCFA receptor-, particularly GPR43-, deficient mice were defective in mounting appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 53 publications
(96 reference statements)
2
61
1
1
Order By: Relevance
“…30 Kim et al reported that GPR43-deficient mice had exacerbated inflammation along with increased frequencies of Th17 cells in animal models of colitis. 31 Similarly, the present study found that administration of butyrate or L. acidophilus both enhanced the expression of GPR41 and GPR43 in the colon and lung in β-Lg allergic mice, along with decreasing IL-4, IL-6, and IL-17 and increasing IFN-γ and TGF-β levels. Importantly, F I G U R E 7 Effect of Lactobacillus acidophilus KLDS 1.0738 on G-protein-coupled receptor 41 (GPR41) and GPR43 mRNA in (a) colon and (b) spleen tissue of β-Lg-sensitized mice.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…30 Kim et al reported that GPR43-deficient mice had exacerbated inflammation along with increased frequencies of Th17 cells in animal models of colitis. 31 Similarly, the present study found that administration of butyrate or L. acidophilus both enhanced the expression of GPR41 and GPR43 in the colon and lung in β-Lg allergic mice, along with decreasing IL-4, IL-6, and IL-17 and increasing IFN-γ and TGF-β levels. Importantly, F I G U R E 7 Effect of Lactobacillus acidophilus KLDS 1.0738 on G-protein-coupled receptor 41 (GPR41) and GPR43 mRNA in (a) colon and (b) spleen tissue of β-Lg-sensitized mice.…”
Section: Discussionsupporting
confidence: 78%
“…Chang et al suggested that the GPR41/43 activated by SCFAs had an important function in the differentiation and/or activation of T lymphocytes . Kim et al reported that GPR43‐deficient mice had exacerbated inflammation along with increased frequencies of Th17 cells in animal models of colitis . Similarly, the present study found that administration of butyrate or L. acidophilus both enhanced the expression of GPR41 and GPR43 in the colon and lung in β‐Lg allergic mice, along with decreasing IL‐4, IL‐6, and IL‐17 and increasing IFN‐γ and TGF‐β levels.…”
Section: Discussionmentioning
confidence: 99%
“…The receptors for SCFA, GPR43, or GPR41 are expressed on epithelial cells, macrophages, and dendritic cells (DCs). Mice deficient in GPR43 were unable to suppress commensal bacterial invasion into colonic tissue and develop chronic Th17‐driven inflammation and intestinal carcinogenesis [32]. Butyrate a SCFA produced by commensal bacteria has anti‐inflammatory properties, stimulating DCs to induce tolerogenic responses in naïve T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary fibre manipulation can very rapidly alter the human gut microbiome, with changes in faecal short chain fatty acid (SCFA) levels seen only one day after the diet reaches the distal gut (6). Dietary fibre can also mediate systemic immune effects (7), as can the microbiota-derived SCFAs (8,9). Furthermore, dietary fibre structures align with phenotypes of specific microbes that differ in their metabolic pathways (10).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, dietary fibre structures align with phenotypes of specific microbes that differ in their metabolic pathways (10). SCFAs are known to confer anti-cancer effects (5,8,9). Other metabolites, including small intermediate and end byproducts of endogenous metabolic pathways, products of microbe-host co-metabolism and exogenous signals arising from diet, drugs and other environmental stimuli might also be important (11).…”
Section: Introductionmentioning
confidence: 99%